Risk Assessment of Clinical Care in Emergency Departments ByHealth Failure Modes and Effects Analysis - Leila Moradi; Abdolhossein Emami Sigaroudi; Majid Pourshaikhian; Mahmoud Heidari (Guilan University of Medical Sciences, 2020)
Introduction: Medical errors are among significant health system problems. The best method to detect errors is to identify the root and systemic causes of errors. Objective: This study aimed to investigate the failures of clinical care in emergency departments using the Healthcare Failure Modes and Effects Analysis (HFMEA). Materials and Methods: This was an analytical and cross-sectional study. The required data were collected qualitatively and quantitatively using focus group discussions in emergency departments. The study population consisted of all emergency department nurses. Study samples were selected by purposive sampling technique. By the HFMEA method, Risk Priority Number (RPN) was calculated to reach failure modes and those with RPN>216 were identified as the most frequent and risky errors.  Results: A total number of 67 failure modes were identified for 26 clinical care processes.The errors with the highest RPN were "the lack of oxygenation during airway suctioning" and "the lack of airway suctioning during ventilator weaning process"; they related to the respiratory system care with RPN=336. The error with the lowest RPN was "the lack of signing verbal orders by two nurses"; related to the general practice with RPN=8. Conclusion: Investigating the causes and effects of these errors, controlling, and suggesting measures indicate the high efficiency of the HFMEA method. It also suggested the preventability of these errors by increasing the knowledge and awareness of the training staff by providing training courses.